1990
DOI: 10.1055/s-2008-1071461
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem Acoustic Evoked Responses: Maturational Aspects from Cochlea to Midbrain

Abstract: BAEPs were recorded from 92 healthy children with a gestational age of 35 weeks up to 16 years. The maturation kinetic of I-III and I-V interpeak latency can well be approximated by the exponential regressions I-V : y = 0.9588 x e -0.9215 x x + 3.9728; r = 0.87; I-III : y = 0.6182 x e -1.1737 x x + 2.1759; r = 0.81; Adult values are reached by about two years of life. In contrast to this immaturity of the central auditory pathways the slopes of latency--intensity functions of waves I and V show no significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 11 publications
0
6
0
2
Order By: Relevance
“…e C ! x ) was chosen based on (1) fi ndings of repeated measures ANOVA analyses, (2) the common use of this function to describe biological processes, (3) the use of exponential functions to describe developmental changes in the acoustically evoked ABR in normally hearing children [Eggermont and Salamy, 1988;Lauffer and Wenzel, 1990;Ponton et al, 1992Ponton et al, , 1996a, thereby allowing comparisons with those analyses, (4) the ability to calculate a time constant (1/C) describing the time course of change, and (5) the assumption that the response does reach a state of maturity (the asymptote, A, of the exponential function provides a prediction of this value). The single exponent curves model one overall process of change.…”
Section: Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…e C ! x ) was chosen based on (1) fi ndings of repeated measures ANOVA analyses, (2) the common use of this function to describe biological processes, (3) the use of exponential functions to describe developmental changes in the acoustically evoked ABR in normally hearing children [Eggermont and Salamy, 1988;Lauffer and Wenzel, 1990;Ponton et al, 1992Ponton et al, , 1996a, thereby allowing comparisons with those analyses, (4) the ability to calculate a time constant (1/C) describing the time course of change, and (5) the assumption that the response does reach a state of maturity (the asymptote, A, of the exponential function provides a prediction of this value). The single exponent curves model one overall process of change.…”
Section: Analysesmentioning
confidence: 99%
“…Values obtained from young children can be fi t to a decreasing exponential function where the asymptote equals the adult values and a developmental time constant can be calculated. By evaluating ABR parameters in this way, it has been suggested that the human auditory brainstem reaches maturation by approximately 1-3 years of age [Eggermont and Salamy, 1988;Gorga et al, 1989;Lauffer and Wenzel, 1990]. For cochlear implant subjects, however, the asymptote of the mature electrically evoked system is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Various parameters of the ABRs are known to change as a function of age or stimulus intensity, thus providing a useful tool to evaluate hearing threshold [Hecox and Galambos, 1974;Roncagliolo et al, 1983;Thivierge and Coté, 1990] and maturity or neurological status of auditory brainstem structures [Salamy et al, 1975;Starr and Hamilton, 1976;Stockard and Rossiter, 1977;Starr, 1978;Mochizuki et al, 1982;Lauffer and Wenzel, 1990;Roncagliolo et al, 1994]. During development the several waves of ABRs progressively increase in amplitude and decrease in both absolute and interpeak latencies (IPLs) [Salamy and McKean, 1976;Starr et al, 1977;Mochizuki et al, 1982;Salamy et al, 1982;Vles et al, 1987;LinaGranade et al, 1993;Ferber-Viart et al, 1996;Roncagliolo et al, 1998].…”
Section: Introductionmentioning
confidence: 99%
“…These features reveal a developing synchrony in the discharges of component fibers and an increase in their conduction velocity due to myelination. Thus ABRs can be considered as an index of CNS maturation [Lauffer and Wenzel, 1990;Jiang et al, 1993;Ichiyama et al, 1995;Roncagliolo et al, 1998]. …”
Section: Introductionmentioning
confidence: 99%
“…Die Eltern [7], gegebenenfalls auch das Kind selbst [5] sollten darauf hingewiesen werden, bei plötzlicher Akzeptanzveränderung baldmöglichst eine aktuelle Kontrolle zu veranlassen: Neben Hörgerätemängeln, Cerumen, otoplastikbedingten Reaktionen im äuße-ren Gehörgang und die im Kindesalter besonders häufigen mittelohrbedingten Hörstörungen wäre hierbei eine In unserem Patientengut war eine nicht korrekte Otoplastikform der Grund für 9% aller Mängel, wobei ein Hörschwellenänderung, etwa im Sinne einer Nachreifung der Hörbahn oder einer Progredienz auszuschließen [8,11,13,15].…”
Section: Introductionunclassified